(untitled) (Eurasian Medical Research Periodical, 2024)
The psychological well-being of an individual is one of the fundamental problems in psychology, which has been of interest throughout the history of psychology as a science. It is especially important to study this area in the context of a changing social situation — the impact of a significant number of anthropogenic and natural factors on humans. One example of such an impact was the COVID-19 pandemic, which affected most of the population of Uzbekistan in 2020 and contributed to a direct and indirect impact on human mental health and cognitive potential.